DOI: 10.22215/etd/2012-06750
|View full text |Cite
|
Sign up to set email alerts
|

Looking for an ounce of prevention : the potential for diagnostic assessment in academic acculturation

Abstract: The author has granted a non exclusive license allowing Library and Archives Canada to reproduce, publish, archive, preserve, conserve, communicate to the public by telecommunication or on the Internet, loan, distrbute and sell theses worldwide, for commercial or non commercial purposes, in microform, paper, electronic and/or any other formats. AVIS: L'auteur a accorde une licence non exclusive permettant a la Bibliotheque et Archives Canada de reproduire, publier, archiver, sauvegarder, conserver, transmettre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 45 publications
(178 reference statements)
0
4
0
Order By: Relevance
“…When it came to a focus on assessment in the transition process, this largely came in the form of an expanding literature exploring post-entry language assessment (PELA) aimed at early identification of at-risk students to help them better adjust to university expectations and have a more successful first-year experience (e.g., Read, 2008Read, , 2016, along with broader disciplinary or academic diagnostic assessments (e.g., Alderson, 2005Alderson, , 2007Fox & Artemeva, 2017;Fox, Haggerty & Artemeva, 2016;Fox, von Randow, and Volkov, 2016;Kajander & Lovric, 2005;McLeod, 2012;Smaill et al, 2012). However, I had not come across very much research on assessment-related changes during the transition to university (i.e., studies that documented and/or compared students' experiences with high school and university assessment).…”
Section: Purpose Goals and Research Questions In This Dissertation Re...mentioning
confidence: 99%
See 3 more Smart Citations
“…When it came to a focus on assessment in the transition process, this largely came in the form of an expanding literature exploring post-entry language assessment (PELA) aimed at early identification of at-risk students to help them better adjust to university expectations and have a more successful first-year experience (e.g., Read, 2008Read, , 2016, along with broader disciplinary or academic diagnostic assessments (e.g., Alderson, 2005Alderson, , 2007Fox & Artemeva, 2017;Fox, Haggerty & Artemeva, 2016;Fox, von Randow, and Volkov, 2016;Kajander & Lovric, 2005;McLeod, 2012;Smaill et al, 2012). However, I had not come across very much research on assessment-related changes during the transition to university (i.e., studies that documented and/or compared students' experiences with high school and university assessment).…”
Section: Purpose Goals and Research Questions In This Dissertation Re...mentioning
confidence: 99%
“…Bonneville-Roussy et al's (2017) study found that students who were autonomously motivated engaged more in coping strategies, and in turn, coping strategies produced more positive career intentions, grades, and affective responses to the stress of assessments. The students in Denison's (1999) study were impacted by their perceptions of fairness and transparency regarding format, administration, specific questions, marking, and feedback, all of which could be motivating or demotivating (see also McLeod, 2012). Palermo et al (2015) probed dietician students' perspectives on their program's competency-based assessments and found that the relationships between the students and their teachers influenced the students' overall experiences in their program and their performance on assessment.…”
Section: Student Motivationmentioning
confidence: 99%
See 2 more Smart Citations